Metrics in soccer - Memmert, D. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
This chapter focuses on simple (e.g., number of sprints, meters run, number of passes) and more complex (e.g., space control, pressing parameters) key performance indicators (KPIs) or metrics. These physiological or tactical indicators try to reflect the performance of athletes in complex environments and in real competition conditions and reflect in different dimensions the complex reality of the sports game or sports performance. Based on these results, performance relevant parameters for training and competition optimization can be analyzed. In the future, experimental approaches can help to test theories and interdisciplinary questions from sports psychology, training science and sports informatics.